Asymmetric information in credit markets and entrepreneurial risk taking - Timo Vesala (Bank of Finland, 2004)
The paper constructs a search-theoretic model of credit markets with a bilateral trading mechanism that enables the manageable introduction of asymmetric information.Borrowers success probabilities are unobservable to financiers, but the degree of risk in observable projects can be used as a sorting device.We find that the efficiency of a perfect Bayesian equilibrium depends negatively/ positively on the credit market tightness /liquidity. In general equilibrium, where the underlying market conditions are endogenously determined, steady states with greater credit market tightness are always associated with increasingly excessive investment in risky projects.Since tighter market conditions also imply less intense competition among financiers, the commonly asserted trade-off between competition and efficiency does not emerge.Tighter monetary policy is shown to worsen the adverse effect of informational frictions on efficiency.
URN:NBN:fi:bof-20140807135
Keywords: 330; credit market; asymmetric information; search; risk taking